A Macro/Micro Decision Model for the Training and Development Specialist - Mealia, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
This article describes a macro/micro decision making model designed to aid the T/D specialist.